2017
DOI: 10.3906/vet-1702-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartum treatment with monensin or propylene glycol mixed with concentrate on milk yield and blood NEFA and BHBA levels in dairy cows

Abstract: Sixty multiparous Holstein-Friesian dairy cows made up the study sample. Group M (n = 20) received 300 mg/day monensin (Kexxtone, Elanco) for 21 days prior to the expected calving date. Group PGC (n = 20) received propylene glycol, mixed with concentrate and fed separately from total mixed ration (TMR) twice a day in the last 21 days of gestation. The control group, Group C (n = 20) did not receive any treatment prior to parturition. Cows in all three groups received PG (300 mL/day) for 5 days after parturitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…It is possible that the PG supplement extracted an impaired fat release from the adipose tissue, a process that was reflected in the milk fat value variation (Borş et al, 2014). Generally, the reduction of milk fat content is in agreement with the most published work as reviewed by Mecitoğlu et al (2017) who suggested that reduced milk fat content could be due to: firstly the decrease in plasma non-esterified fatty acids (NEFA) since lowered NEFA concentrations lead to decreased NEFA-uptake by the mammary gland and secondly the lowest proportion of acetate in the rumen which may reduce the amount of acetate available for devolve fatty acid synthesis in the mammary gland. With regard to protein content, the differences among PG0, PG1 and PG2 groups in protein content of goat milk were not significant at lactation period but PG1 and PG2 goats were more in protein content than PG0 goats.…”
Section: Milk Compositionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is possible that the PG supplement extracted an impaired fat release from the adipose tissue, a process that was reflected in the milk fat value variation (Borş et al, 2014). Generally, the reduction of milk fat content is in agreement with the most published work as reviewed by Mecitoğlu et al (2017) who suggested that reduced milk fat content could be due to: firstly the decrease in plasma non-esterified fatty acids (NEFA) since lowered NEFA concentrations lead to decreased NEFA-uptake by the mammary gland and secondly the lowest proportion of acetate in the rumen which may reduce the amount of acetate available for devolve fatty acid synthesis in the mammary gland. With regard to protein content, the differences among PG0, PG1 and PG2 groups in protein content of goat milk were not significant at lactation period but PG1 and PG2 goats were more in protein content than PG0 goats.…”
Section: Milk Compositionsupporting
confidence: 85%
“…Hence, those authors defined that the milk yield was higher in the PG (10.7 kg/day) group than control (8.4kg/day) group; such increase could be attributed to the energy for milk production increased because of PG supplementation. As well as, Mecitoğlu et al (2017) found that PG caused significantly higher milk yield in 6, 7, 8 weeks (as a late weeks of production), it was 42.52, 43.00 and 44.03kg than 38.82, 39.72 and 38.66 kg in control cows, respectively. Generally, positive effects of PG on milk production are mainly attributed to increases in glycogenic precursors and maintained a moderated metabolic energy status which resulting on bacterial populations that synthesize propionic acid which reflected on milking amount (Melendeza et al, 2018).…”
Section: Milk Yieldmentioning
confidence: 66%
See 1 more Smart Citation
“…The marked decrease in blood plasma urea nitrogen levels in heifers treated with PG or CP or their combination was in line with Mecitoğlu et al (2017) in dairy cows and Abdel-Latif et al (2016) in buffalo treated with PG or CP, they indicated that the reduction in body tissue catabolism may be led to reduce the concentration of serum blood urea nitrogen.…”
Section: As Present In Table (supporting
confidence: 74%
“…In addition, Nalawade et al (2015) discussed that PG had the antibacterial and antifungal effects on many bacteria species. Also, numerous of trials have been conducted that using various PG dosages, in dairy cows (Mecitoğlu et al, 2017). Also, administration in dairy sheep (Santos et al, 2017) caused interpretation of energy balance.…”
Section: Introductionmentioning
confidence: 99%